Developmental maturation of inhibitory control circuitry in a high-risk sample: A longitudinal fMRI study. (June 2020) - Cope, Lora M.; Hardee, Jillian E.; Martz, Meghan E.; Zucker, Robert A.; Nichols, Thomas E.; Heitzeg, Mary M.
Abstract: Background: The goal of this work was to characterize the maturation of inhibitory control brain function from childhood to early adulthood using longitudinal data collected in two cohorts. Methods: Functional MRI during a go/no-go task was conducted in 290 participants, with 88 % undergoing repeated scanning at 1- to 2-year intervals. One group entered the study at age 7–13 years ( n  = 117); the other entered at age 18–23 years ( n  = 173). 33.1 % of the sample had two parents with a substance use disorder (SUD), 43.8 % had one parent with an SUD, and 23.1 % had no parents with an SUD. 1162 scans were completed, covering ages 7–28, with longitudinal data from the cohorts overlapping across ages 16–21. A marginal model with sandwich estimator standard errors was used to characterize voxel-wise age-related changes in hemodynamic response associated with successful inhibitory control. Results: There was significant positive linear activation associated with age in the frontal, temporal, parietal, and occipital cortices. No clusters survived thresholding with negative linear, positive or negative quadratic, or positive or negative cubic contrasts. Conclusions: These findings extend previous cross-sectional and small-scale longitudinal studies that have observed positive linear developmental trajectories of brain function during inhibitory control.